Abstract: This research aimed at finding out how (ex)pre-service students prepare the teaching materials and conduct learning process during teaching practice.In this study, the researcher applied case study as the form of research. The data revealed that - Asdianti, .; Marbun, Rismaya; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research aimed at finding out how (ex)pre-service students prepare the teaching materials and conduct learning process during teaching practice.In this study, the researcher applied case study as the form of research. The data revealed that in the (ex) pre-service students’ teaching experiences, every (ex) pre–service students got different experiences or learning events when teaching practice. This could be seen by their experiences in preparing the learning materials and their experiences in conducting learning process. Generally, the (ex) pre–service students had been ready in preparing materials for their teaching practice class. In choosing teaching media, video and pictures were the favorite teaching media because of the simplicity and the visual object that every student liked. Most of (ex) pre – service students used communicative language teaching (CLT) as their teaching method. However, they still needed to innovate their teaching technique in developing their teaching skill rather than followed the old techniques.   Keywords: Experiences; Teaching practice; Students Abstak: Penelitian ini bertujuan untuk mengetahui bagaimana mahasiswa yang sudah PPL mempersiapkan bahan ajar dan proses belajar selama praktik mengajar. Pada studi ini, peneliti menerapkan studi kasus sebagai bentuk penelitian. Data menunjukkan pada pengalaman mengajar mahasiswa yang telah PPL, setiap mahasiswa PPL punya pengalaman atau peristiwa belajar yang berbeda saat praktik mengajar. Ini terlihat pada pengalaman mereka dalam mempersiapkan materi pembelajaran dan pengalaman mereka dalam melakukan proses pembelajaran. Secara umum, mahasiswa PPL telah siap dalam mempersiapkan bahan karena adanya kelas praktek mengajar sebelum Praktik lapangan. Dalam memilih media pembelajaran, video dan gambar masih menjadi media pengajaran favorit karena kesederhanaan dan objek visualnya yang disukai setiap siswa. Sebagian besar mahasiswa PPL menggunakan pengajaran bahasa komunikatif (CLT) sebagai metode pengajaran mereka. Namun, mereka harus lebih berinovasi dalam menggunakan teknik pengajaran mereka untuk mengembangkan keterampilan mengajar mereka daripada mengikuti teknik lama.   Kata Kunci : Pengalaman, Praktik mengajar, Mahasiswa